New Information and Communication Technologies for climate services: evidence from farmers in Ada East District, Ghana - Sarku, R.; Addi, F.; Attoh, Emmanuel M. N. A. N. (Elsevier, 2025)
How people respond to climate information service (CIS) depends on how information is designed and communicated. While the introduction of new information and communication technologies (ICTs) has improved the delivery of CIS, there are persistent usability challenges, especially among smallholder farmers. This study examined the usability of new ICTs in delivering CIS for farming in Ada East District, Ghana. The research addressed the question, how do smallholder farmers respond to CIS delivered through new ICTs, and what are the usability challenges of these technologies. Using data from document reviews, interviews, and focus group discussions, findings show that farmers predominantly rely on local or indigenous knowledge and traditional ICTs like radio and television for CIS, 7 New ICTs including: Website on weather information, Bulletin on social media: Facebook, WhatsApp weather forecast presented as a flyer, YouTube video on weather information, Short message service (SMS), Audio WhatsApp weather forecast and Weather apps were identified, providing daily, weekly and seasonal forecasts outlooks. However, the utilisation of these new ICTs is relatively limited. Only a few farmers were aware of the delivery of CIS through these new ICTs. Farmers with smartphones are mainly those who access daily and seasonal forecast outlooks using new ICTs, while face-to-face interactions remain the common mode for disseminating information among farmers. Although new ICTs offer forecasts, usability is influenced by the relevance and comprehension of the content, location success and time, typography, symbols and graphics, language clarity, feedback and interactivity and ability to use the new ICT tools. The findings of the study have implications for CIS developers and providers to incorporate design principles such as revision of text structure, font style and size, symbols, wording pattern and word counts. It shed light on the evolving landscape of CIS delivery in farming communities, where traditional methods coexist with emerging digital platforms and provided knowledge on the need to raise awareness on the use of new ICTs with CIS among farmers.